Regional Government Policies with Local Wisdom in Handling the Covid-19 Pandemic in Indonesia - Bernadeta Nefo Eka Wijayanti (Alliance of Health Activists (AloHA), 2022)
The Covid-19 pandemic in Indonesia has been declared a national disaster. The handling of the Covid-19 pandemic in Indonesia, although coordinated nationally by the central government, still involves local governments in making policies to prevent the spread of the Covid-19 virus, and policies in tackling the socio-economic impacts of society. The existence of Regional Autonomy gives the authority to local governments to manage regional potentials and make policies related to the interests of regional communities, however, during a pandemic which is a national disaster, local governments cannot have full authority, there are several things that are under the coordination of the Central Government. The existence of local wisdom is a regional potential. This study wants to find out how the local government's policies are in dealing with the Covid-19 pandemic by paying attention to local wisdom which is a regional potential. This study uses primary data in the form of observations and secondary data in the form of scientific articles in journals that examine related problems, objective information from communication media, related reference books, using descriptive qualitative data analysis. The conclusion shows that there are local government policies in dealing with the Covid-19 pandemic in coordination with the central government, where local governments have the authority to manage, pay attention to local wisdom to empower local communities in policies for handling the Covid-19 pandemic. Keywords: local government policy; local wisdom; Covid-19 pandemic